1988
DOI: 10.1002/polb.1988.090260505
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of manganese(II) and copper(II) salts of poly(ethylene‐co‐methacrylic acid)s

Abstract: The ionic interaction of poly(ethylene‐co‐methacrylic acid) ionomer neutralized with Mn2+ or Cu2+ was studied by ESR spectroscopy to explore the local structure in the ionic aggregate. ESR spectra of the ethylene ionomer were obtained as functions of degree of neutralization and temperature. The existence of both isolated and aggregated cations in the ionomer was confirmed by ESR. In addition, the formation of a Cu2+−Cu2+ dimer structure similar to the crystal structure of copper acetate monohydrate was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This technique is therefore sensitive to the local environment of paramagnetic ions. ESR measurements have been reported for manga nese and copper salts of copolymers of ethylene and methacrylic acid (68). Both isolated and aggregated cations were found, consistent with the presence of both phase dispersed and phase separated ions.…”
Section: Structuresupporting
confidence: 59%
“…This technique is therefore sensitive to the local environment of paramagnetic ions. ESR measurements have been reported for manga nese and copper salts of copolymers of ethylene and methacrylic acid (68). Both isolated and aggregated cations were found, consistent with the presence of both phase dispersed and phase separated ions.…”
Section: Structuresupporting
confidence: 59%
“…Ethylene ionomers are copolymers consisting of methylene sequences as nonpolar segments and a small amount of methacrylic acid or acrylic acid residues as ionic units 1–24. It is well known that the ionic groups are partially or fully neutralized by metal ions such as Zn 2+ , Na + , Ca 2+ , Cu 2+ , or Mn 2+ 1–26.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene ionomers are copolymers consisting of methylene sequences as nonpolar segments and a small amount of methacrylic acid or acrylic acid residues as ionic units 1–24. It is well known that the ionic groups are partially or fully neutralized by metal ions such as Zn 2+ , Na + , Ca 2+ , Cu 2+ , or Mn 2+ 1–26. Because information about the structure and dynamics of ethylene ionomers is indispensable to an understanding of their mechanical, thermal, and other important physical properties, many investigations have been performed with differential scanning calorimetry (DSC),2, 3, 8, 10, 11, 13, 14, 17, 18 X‐ray diffractrometry,2–4, 13, 15, 18, 20, 23, 25, 26 Raman spectroscopy,5, 19 infrared (IR) spectroscopy,7, 8, 13, 19, 22, 24 electron spin resonance spectroscopy,12 dynamic mechanical analysis,13, 14, 17 and dielectric relaxation measurements 13, 16…”
Section: Introductionmentioning
confidence: 99%
“…When the sample is cooled from a temperature above T i to room temperature, the disordered ionic aggregates very slowly transform into the ordered ionic aggregates, with a long relaxation time of about 40 days. We have demonstrated that the order−disorder transition model qualitatively explains most physical properties, but the model has not been universally recognized since direct evidence is not obtained. Moreover, a few other models have been proposed for the change at T i , for example, one relates the change at T i to the melting of quasi-crystallites formed during annealing and another to the evaporation of residual water in the ionomers.…”
Section: Introductionmentioning
confidence: 99%